UJI AKTIVITAS ANTIOKSIDAN SEDIAAN GEL YANG MENGANDUNG EKSTRAK ETANOL DAUN MATOA (Pometia pinnata J. R & G. Forst) DENGAN MENGGUNAKAN METODE DPPH (1,1-Diphenyl-2-Picrylhydrazyl) - Wahyu Margi Sidoretno; Rosa Devitria; Harni Sepriyani (Jurnal Farmanesia, 2021)
Matoa (Pometia pinnata J.R & J. G. Forster) is one of the plants that can be used for traditional medicine. Based on several studies, it is stated that the ethanolic extract of matoa leaves has good antioxidant activity. This study aims to determine the antioxidant activity of gel preparations from the ethanolic extract of matoa (Pometia pinnata) leaves. Matoa leaf extract (Pometia pinnata) was prepared using maceration method with 96% ethanol as solvent. Then the extract was formulated into a gel with 4 formulations, namely F0 (no matoa leaf extract), FI (with 0.1% matoa leaf ethanol extract), FII (with 0.3% matoa leaf extract), FIII (with ethanol leaf matoa by 0.5%). Furthermore, the antioxidant activity test was carried out on the gel samples using the DPPH method (1,1-diphenyl-2-picrylhydrazyl) spectrophotometrically at a wavelength of 515 nm. The results of the antioxidant activity test showed that the percentage of inhibition of the 96% ethanol extract of matoa leaf (Pometia pinnata) was F0 40.34%, FI 55.187%, FII 61.703%, FIII 27.969%, and the percentage inhibition of vitamin C was 178.947%. So it can be said that the matoa leaf extract gel has antioxidant activity.